Educational Game Innovation: Giant Snakes and Ladders with Local Wisdom to Stimulate Pancasila Values in Early Childhood. - Ni Luh Drajati Ekaningtyas (Journal of Psychology and Instruction, 2024)
The rate of delays in early childhood development in Indonesia si quite worrying. It is also feared that the flow of globalization has the potential to diminish children’s love for their homeland, local wisdom values, and the practice of Pancasila values. Therefore, it is necessary to stimulate Pancasila values based on local wisdom in early childhood, but appropriate stimulation media are still very limited. This research aims to develop an educational game in the form of giant snakes and ladders containing local wisdom to stimulate the development of Pancasila values in early childhood. This research is research and development with the ADDIE model. Data collection was carried out using questionnaires, interviews, observation, and documentation. Data analysis was carried out quantitatively and qualitatively. Implementation involved 31 children aged 4-6 years at Kasih Ibu Kindergarten, West Lombok, West Nusa Tenggara. The research results show that the giant snake and ladder that was developed is very feasible and effective in stimulating the development of Pancasila values ​​in early childhood. Children increasingly understand concepts and are able to apply Pancasila values ​​in everyday life after being stimulated by giant snakes and ladders.